2004
DOI: 10.1007/s10096-004-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

Blinded application of microscopy, bacteriological culture, immunoassays and PCR to detect gastrointestinal pathogens from faecal samples of patients with community-acquired diarrhoea

Abstract: A blinded trial in two different laboratories was performed to compare the detection of selected enteric pathogens in 92 unselected faecal samples collected from patients with community-acquired diarrhoea by conventional and PCR-based techniques. Conventional techniques detected a single potential etiological agent in 15% of the samples, whereas results of PCR detected evidence of at least one agent in 41% of the samples. Overall, the detection rates for the different pathogens were as follows: adenovirus sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Baudry et al (1990) first used the aat gene (referred to as the CVD432 EAEC probe) as a target for the identification of EAEC, and claimed that the probe was 89 % sensitive. Although subsequent studies have shown that the sensitivity varies between 15 and 90 % (Okeke & Nataro, 2001), the aat gene has remained the most popular target in molecular assays for the detection of EAEC (Schmidt et al, 1995;Cerna et al, 2003;Pabst et al, 2003;Amar et al, 2004). In this study, seven patients with aatpositive strains were known to have recently travelled outside the UK to destinations that included Nepal, Pakistan, Egypt, Sri Lanka and Mexico.…”
Section: Resultsmentioning
confidence: 88%
“…Baudry et al (1990) first used the aat gene (referred to as the CVD432 EAEC probe) as a target for the identification of EAEC, and claimed that the probe was 89 % sensitive. Although subsequent studies have shown that the sensitivity varies between 15 and 90 % (Okeke & Nataro, 2001), the aat gene has remained the most popular target in molecular assays for the detection of EAEC (Schmidt et al, 1995;Cerna et al, 2003;Pabst et al, 2003;Amar et al, 2004). In this study, seven patients with aatpositive strains were known to have recently travelled outside the UK to destinations that included Nepal, Pakistan, Egypt, Sri Lanka and Mexico.…”
Section: Resultsmentioning
confidence: 88%
“…Given that the PCR detection method was more sensitive than microscopy, particularly when the level of infection was low (McGlade et al, 2003;Amar et al, 2004), only PCR detection data were used to evaluate associations with the other variables (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, considering that the fifty samples selected contain all of microscopy positives, the infection rates observed by immunofluorescence and PCR may overestimate the prevalence of Giardia infection. Nevertheless, more sensitive techniques such as PCR may indeed detect Giardia infection with low parasitic load or evidence the parasite when it is undetectable in stool sample [14,15]. Values of prevalence observed from rural and urban areas are identical, suggesting a comparable risk of infection in both the environment.…”
mentioning
confidence: 99%